ZNFX1: a multifunctional modulator of the innate immune response - Cheng, Li Yi; Parker, Roy (Frontiers in Immunology, 2025)
Recent research has identified ZNFX1 as a critical modulator of the innate immune response. Individuals with loss of function mutations in ZNFX1 have chronic inflammation and increased susceptibility to various pathogens. Several potential functions of ZNFX1 have been proposed, including binding double-stranded RNA to activate antiviral innate immunity, inhibiting the NLRP3 inflammasome, and regulating the stability of host mRNAs. Notably, homologs of ZNFX1 are implicated in innate immunity across a wide range of species, including contributing to transgenerational epigenetic inheritance of small RNA-based defense in C. elegans. In this review, we discuss the significance of ZNFX1 and explore the potential underlying mechanisms that govern its diverse functions.